Non-polar GaN film growth on (0 1 0) gallium oxide substrate by metal organic chemical vapor deposition. Issue 9 (17th April 2017) - Cao, Yu; Li, Ray; Williams, Adam J.; Chu, Rongming; Corrion, Andrea L.; Chang, Ryan
Abstract: Abstract : To achieve the first demonstration of non-polar a -plane gallium nitride (GaN) epitaxy on (0 1 0) gallium oxide substrates by metal organic chemical vapor deposition (MOCVD), a low temperature AlGaN nucleation layer was engineered. Specific low temperature AlGaN growth parameters were necessary because the gallium oxide substrate begins to decompose at ∼600 °C in the ambient of H2 . To achieve a smooth GaN epitaxial surface, low V/III molar ratio, and low pressure were required. To characterize the GaN film, AFM along with an orientation-dependent crystal tilt mosaic study by X-ray diffraction was performed. We effectively reduced threading dislocation density by applying in situ SiN interlayers grown by MOCVD. The oxygen contamination in the GaN film was found to originate from the substrate decomposition during GaN growth and can be reduced more than 10 times by using GaN buffer layer grown under N2 ambient.